(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2012)
Introduction: Isobaric bupivacaine is not routinely practiced as a subarachnoid block, though it may be used as an alternative to traditional hyperbaric solution with less complications and a good operative condition in endoscopic urologic surgery. Objective: This prospective randomized study was conducted over a period of 18 months to evaluate the effects of isobaric bupivacaine with low dose fentanyl in endoscopic urologic surgeries under spinal anaesthesia. Methods: Two equally sized groups (n=60) of male patients were randomly selected and studied for routine endo-urological surgeries under subarachnoid block. One group received 0.5% hyperbaric bupivacaine (HBF) and the other group received 0.5% isobaric bupivacaine (IBF). In both groups bupivacaine was mixed with low dose fentanyl (10 microgram) and 1 ml distilled water. Non-invasive blood pressure, heart rate, SpO2, levels of sensory and motor blockade were recorded frequently. Complications of intrathecal block (if developed) were also recorded and treated. Results: The mean operation time was 49.9±9.55 and 50.10.10±7.98 minutes in HBF and IBF groups respectively and the difference was not statistically significant (p>0.05). The mean time to request for first analgesic was 402.50 ± 37.21 and 288.90±25.22 minutes in HBF and IBF groups respectively and the difference was statistically significant (p<0.001). There was no difference in the level of sensory block and total amount of fluid infused (p>0.05). Base line heart rate and blood pressure of the two studied groups were similar. After the subarachnoid block blood pressure reduced significantly in both the groups (p<0.001) but remained within the acceptable level for the surgery. No significant differences in complications like shivering, nausea, vomiting, hypotension, bradycardia were observed in the groups. Conclusion: Intrathecal isobaric bupivacaine with low dose fentanyl may be used as an alternative to traditional hyperbaric bupivacaine for endoscopic urologic surgeries with less side effects related to intrathecal opioid. DOI: http://dx.doi.org/10.3329/jafmc.v7i2.10394 JAFMC 2011; 7(2): 33-36